1998
DOI: 10.1182/blood.v91.5.1757
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Hodgkin/Reed-Sternberg Cells in Chronic Lymphocytic Leukemia With “Hodgkin's Transformation”

Abstract: A lymphoma with the characteristic features of Hodgkin's disease (HD) occasionally develops in patients with B-cell chronic lymphocytic leukemia (CLL), and has been called Richter's syndrome with HD features. In such cases, large tumor cells have the morphological and immunophenotypic features of classical Hodgkin and Reed-Sternberg (H-RS) cells. However, it is not known whether the H-RS cells arise from transformation of the underlying CLL cells or from a different pathological process. We report herein a stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…There were a total of 88 case reports [1, included in the study (males, 64; females, 21; unknown sex, 2). The majority of classifiable patients belonged to either group 1 or group 2; only 6 patients fit the criteria for group 3, including our case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were a total of 88 case reports [1, included in the study (males, 64; females, 21; unknown sex, 2). The majority of classifiable patients belonged to either group 1 or group 2; only 6 patients fit the criteria for group 3, including our case.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on composite lymphomas involving HD have contributed significantly to our present understanding of the origin of RS cells. Ohno et al [1] studied immunoglobulin heavy-chain gene sequences from RS cells and found then to be identical to those of CLL in two cases of CLL with HD features. A recent study of clonal relationships in CLL and Hodgkin's disease [30] also supports the hypothesis that RSL cells in CLL are clonally related to CLL cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We assessed the clonal relationship between the CLL and the HD-like lesion that developed in the same patient, by single cell analysis. 70 In two out of three cases, the CLL cells and H/RS cells had identical IgH rearrangements as demonstrated by identical sequences in the complementary determining region (CDR) III. Braü ninger and colleagues 71 studied two cases of classical HD, one occurring concurrently with a follicular lymphoma and the other one after a T-cell rich B-cell lymphoma.…”
Section: Additional Observations That Favour a B-lineage Derivation Omentioning
confidence: 93%
“…73 Third, Ohno et al examined the clonal relationship by single cell PCR of IgH gene of HRS cells in HL as RS and B-CLL cells, and demonstrated the same clonal origin of HRS cells and B-CLL cells. 76 Cases of HL unrelated to B-CLL have been reported. 77 Most HL occurring in patients with B-CLL are regarded as clonal evolution of B-CLL, whereas a small number of cases are de novo HL, representing a second malignancy presumably not clonally related to CLL.…”
Section: Rs Other Than Dlbclmentioning
confidence: 99%